2008
DOI: 10.1007/s11172-008-0238-x
|View full text |Cite
|
Sign up to set email alerts
|

New catalytic system Cu(OAc)2—2,4-lutidine—ZnCl2 for olefin cyclopropanation with methyl diazoacetate

Abstract: A new efficient catalytic system consisting of Cu(OAc) 2 , 2,4 lutidine, and ZnCl 2 was found for the cyclopropanation of unsaturated compounds with methyl diazoacetate. In the case of conjugated dienes, the process occurs regioselectively at the most alkylated C=C bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…Gareev et al reported one example of the 1,2-regioselective cyclopropanation of (Z)-1-methyl-1,3-butadiene (1,3-pentadiene) to give the corresponding vinylcyclopropane derivative. 6 The Z ge-ometry reduces the steric repulsion of the double bond, and the rate of 1,2-addition would be improved. 5 However, the study of the 1,2-regioselective cyclopropanation of 1-substituted 1,3-butadienyl derivatives has never advanced very far because of the difficulty of preparing (1Z)-1-substituted 1,3-butadienyl derivatives.…”
mentioning
confidence: 99%
“…Gareev et al reported one example of the 1,2-regioselective cyclopropanation of (Z)-1-methyl-1,3-butadiene (1,3-pentadiene) to give the corresponding vinylcyclopropane derivative. 6 The Z ge-ometry reduces the steric repulsion of the double bond, and the rate of 1,2-addition would be improved. 5 However, the study of the 1,2-regioselective cyclopropanation of 1-substituted 1,3-butadienyl derivatives has never advanced very far because of the difficulty of preparing (1Z)-1-substituted 1,3-butadienyl derivatives.…”
mentioning
confidence: 99%
“…It should be noticed that the Cu(OAc) 2 -2,4-Lut-ZnCl 2 catalytic system in this interaction shows an activity comparable with that in reactions of cyclopropanation of terminal monoolefins (hexane-1) and 1,3-dienes with methyldiazoacetate. Increasing of a carbon chain length leads to decreasing of target ethers yields [8].…”
Section: Resultsmentioning
confidence: 99%